Conductive adhesive layer

By using metal particles A with a melting point below 170°C in the conductive adhesive layer and protruding toward the surface, combining optional alloyed metal particles B and solder particles C, the problem of insufficient adhesion strength under low temperature and short-term crimping conditions in the prior art is solved, and high adhesion strength for metal plates and Ni-Au plating is achieved.

CN119604949APending Publication Date: 2025-03-11TATSUTA ELECTRICWIRE & CABLE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380055322.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing conductive adhesive layer does not have sufficient adhesion strength to the metal plate or Ni-Au plating layer under low temperature and short-term crimping processing conditions.

Method used

An adhesive composition is used that includes metal particles A having a melting point of 170°C or less, and metal particles A protrude to the surface of the conductive adhesive layer, and metal particles B and solder particles C alloyed with metal particles A may be optionally included.

Benefits of technology

Even under low temperature and short-term crimping processing conditions, it is possible to exert high adhesion strength to various adhered objects, especially metal plates or Ni-Au coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604949A_ABST
    Figure CN119604949A_ABST
Patent Text Reader

Abstract

The present invention provides a conductive adhesive layer capable of exhibiting sufficient adhesion strength to various adherends even under low-temperature and short-time crimping processing conditions. The conductive adhesive layer (1) contains a binder component (11) and metal particles A (12a) having a melting point of 170 DEG C or less, and the metal particles A (12a) protrude toward the surface. The conductive adhesive layer (1) preferably further contains metal particles B (12b) that can be alloyed with the metal particles A (12a), and preferably further contains solder particles C (12c). It is preferable that the metal particles A (12a) have a spherical shape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive adhesive layer. Background Art

[0002] Conductive adhesive layers have been conventionally used for connecting electronic components. For example, conductive adhesive layers obtained by alloying low melting point metal particles with high melting point metal particles in order to provide connection stability in place of high temperature solder are known (Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2008-108625 Summary of the invention

[0006] However, conventional conductive adhesive layers have a problem of insufficient adhesion strength under low temperature (eg, 170 to 190° C.) and short-time pressure-bonding conditions, particularly when using a metal plate or a Ni—Au plated layer as an adherend.

[0007] The present invention is made to solve such a problem, and an object of the present invention is to provide a conductive adhesive layer having sufficient adhesion strength to various adherends even under low-temperature and short-time pressure-bonding processing conditions.

[0008] The present inventors have made intensive efforts to solve the above-mentioned problems and have found that a conductive adhesive layer containing metal particles A having a melting point of 170° C. or less and protruding from the surface of the conductive adhesive layer can exhibit high adhesion strength to various adherends even under low-temperature and short-time pressure-bonding processing conditions. The present invention has been completed based on such findings.

[0009] That is, the present invention provides a conductive adhesive layer comprising a binder component and metal particles A having a melting point of 170° C. or less, wherein the metal particles A protrude toward the surface.

[0010] As described above, the conductive adhesive layer contains a binder component and metal particles A having a melting point of 170° C. or less, and the metal particles A protrude from the surface of the conductive adhesive layer, thereby being able to exhibit high adhesion strength to various adherends even under low-temperature, short-time pressure-bonding processing conditions.

[0011] The conductive adhesive layer preferably contains metal particles B capable of alloying with the metal particles A in addition to the metal particles A. By containing the metal particles B, the electrical conductivity and adhesion strength of the conductive adhesive layer can be improved.

[0012] Moreover, the said conductive adhesive layer preferably contains solder particles C in addition to the said metal particles A. By containing the solder particles C, the electrical conductivity in the thickness direction can be improved.

[0013] The metal particles A are preferably in a perfect spherical shape. When the metal particles A are in a perfect spherical shape, the metal particles A are likely to protrude toward the surface of the conductive adhesive layer, and high adhesion strength is likely to be exhibited.

[0014] The metal particles B are preferably in a dendritic or flaky form. When the metal particles B are in a dendritic or flaky form, high adhesion strength can be easily exhibited.

[0015] Furthermore, the solder particles C are preferably in a true spherical shape. By making the solder particles C in a true spherical shape, the electrical conductivity in the thickness direction can be stabilized without variation.

[0016] In addition, the median diameter (D50) of the metal particles A is preferably larger than the thickness of the conductive adhesive layer. By making the median diameter (D50) of the metal particles A larger than the thickness of the conductive adhesive layer, it is easy to exert the adhesion strength under the compression processing conditions at low temperature and short time.

[0017] Furthermore, the thickness of the conductive adhesive layer is preferably 1 to 50 μm.

[0018] The conductive adhesive layer of the present invention can exhibit sufficient adhesion strength to various adherends even under low-temperature and short-time pressure bonding conditions, and can exhibit sufficient adhesion strength even when the adherend is a metal plate or a Ni—Au plated layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a cross-sectional view showing one embodiment of the conductive adhesive layer of the present invention.

[0020] Figure 2 This is a cross-sectional view showing one embodiment of a printed wiring board with a reinforcing member to which a conductive adhesive layer of the present invention is applied. DETAILED DESCRIPTION

[0021] [Conductive adhesive layer]

[0022] The conductive adhesive layer of the present invention contains at least a binder component and metal particles A having a melting point of 170°C or less, and the metal particles A protrude from the surface of the conductive adhesive layer. It should be noted that in this specification, metal particles having a melting point of 170°C or less are referred to as "metal particles A". In addition, in the present invention, "protruding" from the surface of the conductive adhesive layer refers to a state of protruding to a position outside the horizontal plane of the surface of the region where the conductive particles of the adhesive part composed of the binder component do not protrude (specifically, a plane where the height of the surface is averaged) before the binder component flows. For example, the median diameter (D50) of the metal particles A or the particle thickness described later is greater than the thickness of the conductive adhesive layer. It should be noted that the thickness of the conductive adhesive layer refers to the average thickness of the region where the conductive particles of the adhesive part composed of the binder component do not protrude before the binder component flows (for example Figure 1 The conductive adhesive layer may cover the metal particles A or may not cover the metal particles A.

[0023] The conductive adhesive layer may be an anisotropic conductive adhesive layer or an isotropic conductive adhesive layer. For example, when the metal particles A are mainly responsible for conductivity in the conductive adhesive layer, it is an anisotropic conductive adhesive layer, and when the metal particles A and other conductive particles (such as metal particles B described later) are well balanced, it is an isotropic conductive adhesive layer.

[0024] In addition, the conductive adhesive layer preferably contains metal particles B and solder particles C that can be alloyed with the metal particles A. By containing metal particles B and solder particles C that can be alloyed with the metal particles A in addition to the metal particles A, it is easier to exert adhesion strength to various adherends even under low temperature and short time pressure bonding processing conditions.

[0025] Figure 1 One embodiment of the conductive adhesive layer of the present invention is shown. The conductive adhesive layer (1) contains a binder component (11), metal particles A (12a), metal particles B (12b) that can be alloyed with the metal particles A, and solder particles C (12c). The metal particles A (12a) protrude toward the surface of the adhesive layer composed of the binder component (11).

[0026] (Metal Particle A)

[0027] The melting point of the metal particles A is 170°C or less, preferably 160°C or less, and more preferably 150°C or less. In addition, the lower limit of the melting point is not particularly limited, and is preferably 130°C or more, for example. By making the melting point of the metal particles A 170°C or less, it is easy to exert sufficient adhesion strength on various adherends even under low temperature and short time pressure bonding processing conditions. As the metal particles A, only one kind may be used, or two or more kinds may be used.

[0028] The metal particles A are preferably alloys containing tin (melting point: 232°C) and bismuth (melting point: 271°C), and may contain other metals other than tin and bismuth as long as the melting point is within the range of 170°C or less. In addition, the mass ratio of tin to bismuth in the metal particles A is preferably 30:70 to 80:20, more preferably 35:65 to 60:40, and particularly preferably 40:60 to 45:55. By making the mass ratio of tin to bismuth the above, it is easy to adjust the melting point of the metal particles A to be within the range of 130°C to 170°C.

[0029] The median diameter (D50) of the metal particles A is preferably larger than the thickness of the conductive adhesive layer, preferably 70 to 500% relative to the thickness of the conductive adhesive layer, more preferably 100 to 400%, and particularly preferably 150 to 300%. By making the median diameter (D50) of the metal particles A larger than the thickness of the conductive adhesive layer (especially more than 70% of the thickness of the conductive adhesive layer), it is easy to have metal particles A whose maximum particle diameter is larger than the thickness of the conductive adhesive layer. As a result, the metal particles A protrude from the surface of the conductive adhesive layer, and when the metal particles A are adhered to the adherend, the metal particles A are appropriately dissolved, and the adhesion strength can be exerted even under low temperature conditions. In addition, the median diameter (D50) of the metal particles A is more than 100% of the thickness of the conductive adhesive layer, so that the median diameter (D50) of the metal particles A becomes larger than the thickness of the conductive adhesive layer, and it becomes easy to protrude from the surface. If the median diameter (D50) of the metal particles A is 500% or less of the thickness of the conductive adhesive layer, the adhesion strength to the adherend is further excellent. It should be noted that in this specification, the thickness of the conductive adhesive layer refers to the average thickness of the region where the metal particles do not protrude from the adhesive portion composed of the adhesive component before the adhesive component flows.

[0030] In addition, the thickness of the conductive adhesive layer is preferably greater than the thickness of the conductive adhesive layer, preferably 100 to 400%, more preferably 150 to 300%, relative to the thickness of the conductive adhesive layer. By making the particle thickness greater than the thickness of the conductive adhesive layer, the metal particles A can be more easily protruded from the surface.

[0031] The median diameter (D50) of the metal particles A is preferably 3 to 150 μm, more preferably 5 to 100 μm, and particularly preferably 10 to 75 μm. When the median diameter (D50) of the metal particles A is within the above range, the metal particles A can easily protrude toward the surface of the conductive adhesive layer.

[0032] The shape of the metal particles A may be spherical (perfect spherical, elliptical, etc.), flake (scaly, flat), dendritic (dendritic), fibrous, irregular (polyhedral), etc. Among them, from the viewpoint of making it easy for the metal particles A to protrude to the surface of the conductive adhesive layer, a spherical shape is preferred, and a perfect spherical shape is particularly preferred.

[0033] The content of the metal particles A is preferably 50 to 500 parts by mass, more preferably 60 to 400 parts by mass, particularly preferably 70 to 300 parts by mass, and particularly preferably 80 to 200 parts by mass, relative to 100 parts by mass of the binder component. By making the content of the metal particles A within the above range, a sufficient amount of the metal particles A is included, and it becomes easy to protrude to the surface of the conductive adhesive layer, and it is easy to exert the adhesion strength.

[0034] (Metal Particle B)

[0035] The conductive adhesive layer of the present invention may contain other metal particles other than the above-mentioned metal particles A. Among them, as the above-mentioned other metal particles, it is preferable to contain metal particles that can be alloyed with the metal particles A. It should be noted that in this specification, the metal particles that can be alloyed with the metal particles A are referred to as "metal particles B that can be alloyed with the metal particles A" or "metal particles B". As the above-mentioned metal particles B, only one kind may be used, or two or more kinds may be used.

[0036] Examples of the metal particles B include metal particles, metal-coated metal particles, metal-coated resin particles, metal-coated graphite particles, metal-coated alloy particles, resin-coated metal particles, and metal fibers.

[0037] Examples of the metal particles B include copper particles, silver-coated copper particles, silver-coated copper alloy particles, nickel particles, silver-coated nickel particles, silver-coated graphite particles, copper-coated graphite particles, resin-coated silver particles, resin-coated copper particles, resin-coated nickel particles, etc. Among them, metal particles containing copper are preferred, and copper particles and silver-coated copper particles are particularly preferred, from the viewpoint of alloying with the metal particles A, improving the electrical conductivity of the conductive adhesive layer, and exerting sufficient adhesion strength under low temperature and short-time pressure-bonding processing conditions.

[0038] As the shape of the above-mentioned metal particles B, spherical (perfect spherical, elliptical, etc.), flake (scaly, flat), dendritic (dendritic), fibrous, irregular (polyhedral) and the like can be cited. Among them, preferably flake, dendritic. By making the shape of the above-mentioned metal particles B flake, dendritic, so that it is easy to take the posture of the above-mentioned metal particles B overlapping each other, thereby increasing the contact between the above-mentioned metal particles B and improving the conductivity in the plane direction. The improvement of the conductivity in the plane direction is combined with the conductivity in the thickness direction based on the metal particles A, and the conductivity of the conductive adhesive layer as a whole is improved (electrical stability), and the connection stability between the adherends can be further improved. In addition, the above-mentioned metal particles A are melted and alloyed, and the metal particles B that can be alloyed with the above-mentioned metal particles A are connected in the conductive adhesive layer, thereby being able to exert the adhesion strength.

[0039] The median diameter (D50) of the metal particles B is preferably smaller than that of the metal particles A, specifically, preferably 0.5 to 25 μm, more preferably 3 to 10 μm. If the median diameter (D50) is 0.5 μm or more, isotropic conductivity can be further exerted. In addition, the metal particles B have good dispersibility and can suppress aggregation. If the median diameter (D50) is smaller than the metal particles A (especially if it is 25 μm or less), the conductive adhesive layer has a further excellent adhesion strength to the adherend.

[0040] The content of the metal particles B is preferably less than that of the metal particles A, preferably 30 to 300 parts by mass, more preferably 40 to 250 parts by mass, particularly preferably 50 to 200 parts by mass, and particularly preferably 60 to 150 parts by mass, relative to 100 parts by mass of the binder component. By making the content of the metal particles B within the above range, it is easy to exert the adhesion strength.

[0041] (Solder particles C)

[0042] The conductive adhesive layer of the present invention preferably contains solder particles as the other metal particles. In particular, it is preferred to contain solder particles in addition to the metal particles A and the metal particles B. It should be noted that in this specification, the solder particles are referred to as "solder particles C". As the solder particles C, only one type may be used, or two or more types may be used.

[0043] The above-mentioned solder particles C preferably contain at least tin as a constituent metal. The content ratio of tin in the solder particles C is preferably 80% by mass or more relative to the total amount 100% by mass of the solder particles C, more preferably 85% by mass or more, further preferably 90% by mass or more, and particularly preferably 94% by mass or more. The tin in the solder particles C is inferred to be a substance that forms an alloy on the interface with an adherend (ground circuit, reinforcing member on the ground side, etc.) having conductivity during thermocompression bonding. Therefore, if the solder particles C contain 80% by mass or more (especially 90% by mass or more) of tin, the connection stability of the adherends can be maintained when high temperature is applied in the reflow process, etc. The above-mentioned content ratio is preferably 99.9% by mass or less, more preferably 99.6% by mass or less. If the above-mentioned content ratio is 99.9% by mass or less, the solder particles C have a certain degree of hardness, and the solder particles C will not be overly compressed when high pressure is applied under high temperature conditions, and it is easy to ensure the conduction between the adherends.

[0044] In addition, as a constituent metal of the solder particles C, other metals other than tin may be included. Examples of the other metals include gold, silver, copper, platinum, nickel, zinc, lead, palladium, bismuth, antimony, and indium. From the viewpoint of further excellent connection stability, the solder particles C preferably include metals harder than tin such as gold, silver, copper, platinum, nickel, and palladium. The other metals may each include only one or more.

[0045] The shape of the solder particles C may be spherical (perfect spherical, elliptical, etc.), flake (scaly, flat), dendritic (dendritic), fibrous, irregular (polyhedral), etc. Among them, from the viewpoint of connection resistance, a spherical shape is preferred, and a perfect spherical shape is particularly preferred.

[0046] The median diameter (D50) of the solder particles C is preferably larger than that of the metal particles B, preferably 1 to 150 μm, more preferably 3 to 150 μm, further preferably 5 to 100 μm, further preferably 5 to 90 μm, and particularly preferably 10 to 75 μm. If the median diameter (D50) is larger than the metal particles B (especially if it is 1 μm or more), the conductivity in the thickness direction can be further exerted by the solder particles C. In addition, the metal particles have good dispersibility and can suppress aggregation. If the median diameter (D50) is 150 μm or less (especially 90 μm or less), the adhesion strength to the adherend of the conductive adhesive layer is further excellent.

[0047] The content of the solder particles C is preferably greater than that of the metal particles B, preferably 50 to 500 parts by mass, more preferably 60 to 400 parts by mass, particularly preferably 70 to 300 parts by mass, and particularly preferably 80 to 200 parts by mass, relative to 100 parts by mass of the binder component. By making the content of the solder particles C greater than that of the metal particles B (particularly within the above range), it is easy to exert the adhesion strength even under low temperature and short time crimping processing conditions.

[0048] In addition, the conductive adhesive layer may contain other metal particles other than the metal particles A, metal particles B and solder particles C. The total amount of the metal particles A, metal particles B and solder particles C is preferably 90% by mass or more, more preferably 100% by mass, in the total amount of 100% by mass of the metal particles used in the conductive adhesive layer. By making the total amount of the metal particles A, metal particles B and solder particles C within the above range, it is easy to exert a higher adhesion strength.

[0049] The total content of the metal particles is preferably 80 to 1000 parts by mass relative to 100 parts by mass of the binder component, more preferably 100 to 1000 parts by mass, further preferably 120 to 700 parts by mass, and particularly preferably 150 to 400 parts by mass. By making the total content of the metal particles 80 parts by mass or more relative to 100 parts by mass of the binder component, it is easy to exert conductivity, and by making the total content of the metal particles 100 parts by mass or less relative to 1000 parts by mass of the binder component, it is easy to exert sufficient adhesion strength.

[0050] (Binder ingredients)

[0051] Examples of the binder component include thermoplastic resins, thermosetting resins, active energy ray-curable compounds, etc. The binder component may be used alone or in combination of two or more.

[0052] Examples of the thermoplastic resin include polystyrene resins, vinyl acetate resins, polyester resins, polyolefin resins (e.g., polyethylene resins, polypropylene resin compositions, etc.), polyimide resins, acrylic resins, etc. The thermoplastic resins may be used alone or in combination of two or more.

[0053] As the thermosetting resin, both thermosetting resins (thermosetting resins) and resins obtained by curing the thermosetting resins can be cited. As the thermosetting resin, for example, phenolic resins, epoxy resins, polyurethane resins, melamine resins, alkyd resins, etc. can be cited. The thermosetting resins can be used alone or in combination of two or more.

[0054] Examples of the epoxy resin include bisphenol epoxy resins, spiro epoxy resins, naphthalene epoxy resins, biphenyl epoxy resins, terpene epoxy resins, glycidyl ether epoxy resins, glycidyl amine epoxy resins, and novolac epoxy resins.

[0055] Examples of the bisphenol type epoxy resin include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, tetrabromobisphenol A type epoxy resin, and the like. Examples of the glycidyl ether type epoxy resin include tris(glycidyloxyphenyl)methane, tetra(glycidyloxyphenyl)ethane, and the like. Examples of the glycidyl amine type epoxy resin include tetraglycidyldiaminodiphenylmethane, and the like. Examples of the novolac type epoxy resin include cresol novolac type epoxy resin, phenol novolac type epoxy resin, α-naphthol novolac type epoxy resin, and brominated phenol novolac type epoxy resin, and the like.

[0056] The above-mentioned active energy ray-curable compound may include a compound that can be cured by irradiation with active energy rays (active energy ray-curable compound) and a compound obtained by curing the above-mentioned active energy ray-curable compound. The active energy ray-curable compound is not particularly limited, and examples thereof include polymerizable compounds having one or more (preferably two or more) free radical reactive groups (such as (meth) acryloyl groups) in the molecule. The above-mentioned active energy ray-curable compound may be used alone or in combination of two or more.

[0057] As the above-mentioned adhesive component, a thermosetting resin is preferably used. In this case, after configuring a conductive adhesive layer on an adherend such as a printed wiring board or a shielded printed wiring board that implements electromagnetic wave shielding countermeasures, the adhesive component can be cured by pressurization and heating, which will make the adhesion of the bonding portion good. For example, when the adhesive component is a thermosetting resin, the adhesive component after thermal compression bonding is a thermosetting resin cured by the above-mentioned thermosetting resin.

[0058] When the binder component includes a thermosetting resin, a curing agent for promoting a thermosetting reaction may be included as a component constituting the binder component. The curing agent may be appropriately selected according to the type of the thermosetting resin. Only one type of curing agent may be used, or two or more types of curing agents may be used.

[0059] The content of the binder component of the conductive adhesive layer is preferably 15 to 95% by mass relative to the total amount 100% by mass of the conductive adhesive layer, more preferably 20 to 90% by mass, and further preferably 30 to 80% by mass. If the content is 15% by mass or more, the adhesion to the adherend is better. If the content is 95% by mass or less, the metal particles A can be fully matched, and the adhesion strength and conductivity are further excellent.

[0060] In the range of not damaging the effect of the present invention as the purpose, the above-mentioned conductive adhesive layer may contain other components other than the above-mentioned components. As the above-mentioned other components, components contained in known or even conventional adhesives can be cited. As the above-mentioned other components, for example, curing accelerators, plasticizers, flame retardants, defoamers, viscosity modifiers, antioxidants, diluents, anti-settling agents, fillers, colorants, leveling agents, coupling agents, ultraviolet light absorbers, tackifying resins, anti-blocking agents, etc. can be cited. The above-mentioned other components can be used only one, or two or more.

[0061] The thickness of the conductive adhesive layer is preferably 3 to 50 μm, more preferably 5 to 30 μm. If the thickness is 3 μm or more, the adhesion strength to the adherend is better. If the thickness is 50 μm or less, the cost can be controlled, and the product with the conductive adhesive layer can be designed to be very thin. It should be noted that the thickness of the conductive adhesive layer is the thickness of the area where the metal particles A do not protrude. In addition, the thickness of the conductive adhesive layer after pressing is preferably also within the above range.

[0062] Regarding the above-mentioned conductive adhesive layer, it can be obtained by a peel test under the conditions of a tensile speed of 50 mm / min and a peeling angle of 90° at room temperature. The adhesion strength (peel force) relative to the metal plate or the Ni-Au plating is not particularly limited, but is preferably 7.3 N / cm or more, more preferably 8.0 N / cm or more, further preferably 9.0 N / cm or more, and particularly preferably 10.0 N / cm or more. If the above-mentioned adhesion strength is 7.3 N / cm or more, the adhesion to the adherend of the above-mentioned conductive adhesive layer is further excellent. The above-mentioned Ni-Au plating can be reinforced with a plastic film or the like in a manner that does not break during the peel test. The specific method of the above-mentioned peel test is described in the embodiments described later.

[0063] The conductive adhesive layer may be laminated with a separation film on at least one side. That is, the conductive adhesive layer may be provided as a laminated body, the laminated body comprising a separation film and the conductive adhesive layer formed on the release surface of the separation film. The separation film is peeled off when used.

[0064] The conductive adhesive layer can be produced by a known or customary production method, for example, by coating an adhesive composition to form a conductive adhesive layer on a temporary substrate such as a release membrane or a substrate, and removing the solvent and / or partially curing the adhesive composition as required.

[0065] The adhesive composition, for example, contains a solvent (solvent) in addition to the components contained in the conductive adhesive layer. Examples of the solvent include toluene, acetone, butanone, methanol, ethanol, propanol, dimethylformamide, etc. The solid content concentration of the adhesive composition can be appropriately set according to the thickness of the conductive adhesive layer to be formed.

[0066] The adhesive composition can be applied by a known coating method, for example, a coating machine such as a gravure roll coater, a reverse roll coater, a lick roll coater, a lip die extrusion coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, a direct coater, or a slit coater can be used.

[0067] The conductive adhesive layer produced as described above can exhibit sufficient adhesion strength to various adherends, especially metal plates or Ni-Au plated layers, under low-temperature and short-time pressure bonding conditions, and can therefore be preferably used for through-hole filling of printed wiring boards and as a resist ink.

[0068] [Printed wiring board with reinforcement member]

[0069] Figure 2 The following is an example of applying the above conductive adhesive layer to a printed wiring board with a reinforcing member. Figure 2 As shown, a printed wiring board with a reinforcing component (X) of one embodiment of a printed wiring board with a reinforcing component comprises: a printed wiring board (3), a conductive adhesive layer (1') provided on the printed wiring board (3), and a conductive reinforcing component (2) provided on the conductive adhesive layer (1').

[0070] The printed wiring board (3) comprises a base member (31), a circuit pattern (32) partially provided on the surface of the base member (31), an insulating protective layer (33) covering the circuit pattern (32) for insulation protection, and an adhesive (34) covering the circuit pattern (32) and used for bonding the circuit pattern (32) to the base member (31) and the insulating protective layer (33). The circuit pattern (32) comprises a plurality of signal circuits (32a) and a ground circuit (32b). The adhesive (34) on the ground circuit (32b) and the insulating protective layer (33) are provided with an opening (through hole) (3a) penetrating the adhesive (34) and the insulating protective layer (33) in the thickness direction.

[0071] The conductive adhesive layer (1') is bonded to the surface of the insulating protective layer (33) of the printed wiring board (3) in a manner that covers and plugs the opening (3a), and the adhesive component (11') fills the opening (3a). The conductive adhesive layer (1') is formed by metal particles A (12a), metal particles B (12b), solder particles C (12c) and adhesive components (11'). The conductive adhesive layer (1') has a thick film portion in which the thickness of the adhesive layer is relatively thick and a thin film portion in which the thickness of the adhesive layer is relatively thin. The thick film portion is consistent with the portion that fills the opening (3a), and the thin film portion is consistent with the portion located between the insulating protective layer (33) and the reinforcing component (2). The metal particles A (12a) and the solder particles C (12c) in the thick film portion are located between the reinforcing component (2) and the grounding circuit (32b), and preferably contact and conduct the reinforcing component (2) and the grounding circuit (32b). In addition, the metal particles A (12a) protruding from the surface of the conductive adhesive layer (1') are in close contact with the ground circuit (32b) and the surface of the reinforcing member (2). In addition, by containing the metal particles B (12b) and the solder particles C (12c), the grounding member (32b) and the reinforcing member (2) are electrically connected, and the reinforcing member (2) functions as an external connection conductive layer, and the surface of the reinforcing member (2) is electrically connected to the external grounding member.

[0072] Regarding the conductive adhesive layer (1'), for example, the conductive adhesive layer (1) before flowing or curing that forms the conductive adhesive layer (1') is adhered to the surface of the reinforcing component (2) as needed, and then adhered to the insulating protective layer (33) in the printed wiring board (3), and then the adhesive component (11) is made to flow or cure by heating and hot pressing is performed, thereby causing a part of the metal particles A (12a) and the solder particles C (12c) to be sandwiched between the reinforcing component (2) and the insulating protective layer (33) and compressively deformed, while the adhesive component (adhesive component) (11) is adhered to the insulating protective layer (33) and the adhesive component (11) is made to flow to fill the adhesive component (11), the metal particles A (12a), the metal particles B (12b), and the solder particles C (12c) into the opening (3a), and can be cured as needed to form the adhesive component (11').

[0073] An electronic component (4) is connected to a mounting portion provided on a surface of a printed circuit board (3) opposite to the reinforcing component (2). The mounting portion where the reinforcing component (2) and the electronic component (4) are connected is arranged relative to each other. Thus, the reinforcing component (2) strengthens the mounting portion of the electronic component (4). The reinforcing component (2) having conductivity is electrically connected to a grounding circuit (32b) of the printed circuit board (3) via a conductive adhesive layer (1'). Thus, the reinforcing component (2) and the grounding circuit (32) maintain the same potential, thereby shielding the mounting portion of the electronic component (4) from noise such as electromagnetic waves from the outside.

[0074] Example

[0075] Hereinafter, one embodiment of the present invention will be described in more detail based on examples. It should be noted that the unit of the content of each component shown in Table 1 is "parts by mass".

[0076] Example 1

[0077] 100 parts by mass of bisphenol A epoxy resin (trade name "jER1256", manufactured by Mitsubishi Chemical Corporation) and 111 parts by mass of metal particles A (Sn-Bi alloy metal particles, Sn:Bi=42:58, melting point 138°C, average particle size 35 μm, spherical) were mixed in an organic solvent (toluene) to a solid content of 20% by mass, and stirred and mixed to prepare an adhesive composition. The obtained adhesive composition was applied to the release-treated surface of a PET film whose surface had been subjected to a release treatment, and the solvent was removed by heating, thereby forming a conductive adhesive layer with a thickness of 20 μm and metal particles A protruding from the surface.

[0078] Examples 2 to 7, Comparative Examples 1 to 3

[0079] A conductive adhesive layer was prepared in the same manner as in Example 1 except that the type, shape, blending amount, etc. of the metal particles in the conductive adhesive layer were changed as shown in Table 1. The details of each component in the table are as follows.

[0080] Metal particles B: Silver-coated copper particles, median diameter (D50) 5 μm

[0081] Solder particles C: Sn96.5-Ag3.0-Cu0.5 metal particles (Sn:Ag:Cu=96.5:3.0:0.5, melting point 217°C, median diameter (D50) 35μm

[0082] [evaluate]

[0083] The following evaluations were performed on the conductive adhesive layers produced using the metal particles used in the above-mentioned Examples and Comparative Examples.

[0084] (1) Median diameter (D50)

[0085] The median diameter (D50) of the metal particles was measured using a flow particle image analyzer (trade name "FPIA-3000", manufactured by Sysmex Corporation). Specifically, a 10x objective lens and a bright field optical system were used, and the measurement was performed using a metal particle dispersion adjusted to a concentration of 4000 to 20000 particles / μl by the LPF measurement mode. The above-mentioned metal particle dispersion was prepared by adding 0.1 to 0.5 ml of a surfactant to an aqueous solution of sodium hexametaphosphate adjusted to 0.2% by mass and adding 0.1±0.01 g of metal particles as a measurement sample. The suspension in which the metal particles are dispersed is subjected to a dispersion treatment for 1 to 3 minutes using an ultrasonic disperser for measurement. The median diameter (D50) of the metal particles obtained by the measurement is shown in Table 1.

[0086] (2) Sealing strength

[0087] The conductive adhesive layer and SUS metal reinforcement plate (thickness: 200 μm) prepared in the examples and comparative examples were heated and pressurized using a pressing machine at a temperature of 120°C, a time of 5 seconds, and a pressure of 0.5 MPa. After further heating at 150°C for 1 hour, the PET film was peeled off to prepare a metal reinforcement plate with a conductive adhesive layer.

[0088] Next, the Ni-Au plated layer of the laminated film having a base substrate composed of polyimide, a copper foil formed on the surface of the base substrate, and a Ni-Au plated layer formed on the surface of the copper foil and the metal reinforcing plate with a conductive adhesive layer were bonded by a press machine at a temperature of 170°C, a time of 60 seconds, and a pressure of 2MPa, and then further pressed by a press machine at a temperature of 170°C, a time of 180 seconds, and a pressure of 2MPa to produce a laminated film with a metal reinforcing plate. Next, the laminated film with a metal reinforcing plate was fixed to a measuring table with a double-sided adhesive sheet, and the laminated film was peeled off from the conductive adhesive layer at room temperature using a tensile tester (trade name "AGS-X50S", manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min and a peeling angle of 90°, and the maximum value of the peel strength at break was measured.

[0089] (3) Thickness of the conductive adhesive layer after pressing

[0090] The thickness of the conductive adhesive layer subjected to the press working as described above was measured using a digital micrometer (trade name "PMU-150-50MX", manufactured by Mitutoyo Corporation).

[0091] Table 1

[0092]

[0093] It can be confirmed that the conductive adhesive layer of Examples 1 to 7 has a particle thickness greater than the thickness of the layer, and the metal particles A having a melting point of 170°C or less protrude from the surface of the layer, so that the adherend is a Ni-Au plated layer and exhibits good adhesion strength even under low-temperature, short-time compression processing conditions. On the other hand, it can be confirmed that in the case where the metal particles A are not contained (Comparative Examples 1 and 3) or the particle thickness of the metal particles A is less than the thickness of the conductive adhesive layer and does not protrude from the surface of the layer, sufficient adhesion strength cannot be exhibited for the Ni-Au plated layer under low-temperature, short-time compression processing conditions (Comparative Example 2).

[0094] Modifications of the present invention will be disclosed below.

[0095] [Note 1]

[0096] A conductive adhesive layer comprising a binder component and metal particles A having a melting point of 170° C. or less,

[0097] The metal particles A protrude toward the surface.

[0098] [Note 2]

[0099] The conductive adhesive layer according to Supplementary Note 1, further comprising metal particles B capable of alloying with the metal particles A.

[0100] [Note 3]

[0101] The conductive adhesive layer according to Appendix 1 or 2, further comprising solder particles C.

[0102] [Note 4]

[0103] The conductive adhesive layer according to any one of Appendixes 1 to 3, wherein the metal particles A are true spherical.

[0104] [Note 5]

[0105] The conductive adhesive layer according to any one of Appendixes 2 to 4, wherein the metal particles B are dendritic or flaky.

[0106] [Note 6]

[0107] The conductive adhesive layer according to any one of Appendixes 3 to 5, wherein the solder particles C are true spherical.

[0108] [Note 7]

[0109] The conductive adhesive layer according to any one of Appendixes 1 to 6, wherein a median diameter (D50) of the metal particles A is larger than a film thickness of the conductive adhesive layer.

[0110] [Note 8]

[0111] The conductive adhesive layer according to any one of Appendixes 1 to 7, wherein the thickness is 1 to 50 μm.

[0112] Explanation of symbols

[0113] X Printed wiring board with reinforcement

[0114] 1, 1' Conductive adhesive layer

[0115] 11, 11' Binder composition

[0116] 12a Metal Particle A

[0117] 12b Metal Particle B

[0118] 12c Solder particles C

[0119] 2 Strengthening components

[0120] 3 Printed wiring board

[0121] 31 Base parts

[0122] 32 Circuit Pattern

[0123] 32a Signal circuit

[0124] 32b Grounding circuit

[0125] 33 Insulation protective layer

[0126] 34 Adhesive

[0127] 4 Electronic components

Claims

1. A conductive adhesive layer comprising a binder component and metal particles A having a melting point of 170° C. or less, The metal particles A protrude toward the surface.

2. The conductive adhesive layer according to claim 1, wherein Metal particles B capable of being alloyed with the metal particles A are also included.

3. The conductive adhesive layer according to claim 1 or 2, wherein Solder particles C are also included.

4. The conductive adhesive layer according to claim 1 or 2, wherein The metal particles A are spherical.

5. The conductive adhesive layer according to claim 2, wherein The metal particles B are in the form of dendrites or flakes.

6. The conductive adhesive layer according to claim 3, wherein The solder particles C are in the shape of true spheres.

7. The conductive adhesive layer according to claim 1 or 2, wherein The median diameter D50 of the metal particles A is larger than the thickness of the conductive adhesive layer. 8 . The conductive adhesive layer according to claim 1 , which has a thickness of 1 to 50 μm.

Citation Information

Patent Citations

  • Conductive adhesive

    JP2008108625A